The macroprudential measures for mitigating the effects of the pandemic crisis in tourism economies - Popek Biškupec, Petra; Herman, Suzana; Ružić, Ivan (Business, Management and Economics Engineering, 2022)
Purpose – The paper evaluates the applied macroprudential measures in selected countries by testing their efficiency in tourism and reducing the revenue gap in tourism sector during the pandemic crisis.Research methodology – The effects of macroprudential policy were tested using the Granger causality test and PVAR model. The research used data from the period 2019 to 2022 by quarters. The impulse response function evaluated the long run impact of macroprudential policy on performance of tourism entities.Findings – The results confirm the positive effect of systemically important institutions buffer (SIB) on reducing the losses in tourism. The impulse response showed the significant impact of SIB on revenue gap (RG) reduction.Research limitations – The research has limitations regarding to the short period of observation. The additional variables can be entered into the model.Practical implications – The results serve the policy makers for shaping the measures for recovery policies and maintaining long-term economic stability. The findings are useful as they can serve as a guide in designing measures to help the tourism recovery.Originality/Value – The contribution of this study is reflected in providing scientific evidence of macroprudential measures effectiveness for several countries and routing policies for tourism recovery.